1986
DOI: 10.1073/pnas.83.15.5558
|View full text |Cite
|
Sign up to set email alerts
|

recD: the gene for an essential third subunit of exonuclease V.

Abstract: Exonuclease V (EC 3.1.11.5) of Escherichia coli, an enzyme with multiple activities promoting genetic recombination, has previously been shown to contain two polypeptides, the products of the recB and recC genes. We report here that the enzyme contains in addition a third polypeptide (a) with a molecular mass of about 58 kDa. The a poypeptide is not synthesized by a class of mutants (previously designated recB*) lacking the nuclease activity of exonuclease V but retaining recombination proficiency. The gene, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
199
0
3

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(211 citation statements)
references
References 35 publications
9
199
0
3
Order By: Relevance
“…The former possibility is consistent with the observation that, although the enzyme appears to be greater than 95% pure on Coomassie-stained gels, the specific activity of our preparation is approximately 11% of that of Amundsen et al (1986), who report the highest specific activity found in the literature (fraction V, 3 X lo5 nuclease units/mg of protein). Our specific activity falls within the range reported by other laboratories (2.1 X lo4 to 2.7 X lo5 nuclease units/mg of protein; Nobrega et al, 1972;Ponticelli et al, 1985;Taylor & Smith, 1985;Hermanns & Wackernagel, 1977;Dykstra et al, 1984).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The former possibility is consistent with the observation that, although the enzyme appears to be greater than 95% pure on Coomassie-stained gels, the specific activity of our preparation is approximately 11% of that of Amundsen et al (1986), who report the highest specific activity found in the literature (fraction V, 3 X lo5 nuclease units/mg of protein). Our specific activity falls within the range reported by other laboratories (2.1 X lo4 to 2.7 X lo5 nuclease units/mg of protein; Nobrega et al, 1972;Ponticelli et al, 1985;Taylor & Smith, 1985;Hermanns & Wackernagel, 1977;Dykstra et al, 1984).…”
Section: Resultssupporting
confidence: 93%
“…Our value is similar to that of fraction IV of Amundsen et al (1986) and those of Ponticelli et al (1985) and Taylor and Smith (1985). Assuming a molecular weight of 330K for recBCD enzyme, our preparation was calculated to have 5.4 X loio enzyme molecules/unit of nuclease activity or 1.12 x IO4 units/nmol of enzyme.…”
Section: Roman and Kowalczykowskisupporting
confidence: 92%
See 2 more Smart Citations
“…recC mutants are recombination deficient, recD mutants are recombination proficient (Chaudhury and Smith, 1984;Amundsen et al, 1986;Thaler et al, 1989) and that the χ stimulation is not detected in recD mutants (Chaudhury and Smith, 1984). The nuclease activity of RecBCD enzyme is undetectable in cell-free extracts prepared from recD mutants (Chaudhury and Smith, 1984).…”
Section: Introductionmentioning
confidence: 98%